2002
DOI: 10.1007/s00041-002-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

Clifford Analysis Techniques for Spherical PDE

Abstract: For α ∈ R, the class of α−order spherical harmonic functions in an open setis the spherical Laplace-Beltrami operator of order α and s is the radially independent part of the Laplace operator. We obtain a Green's integral formula for the functions in H α ( ) with kernel expressed as a Gegenbauer function. As generalizations, higher order spherical iterated Dirac operators are defined in a polynomial form. Integral representations of the null solutions to these operators and an intertwining formula relating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 15 publications
1
64
0
Order By: Relevance
“…In this way one constructs other examples of conformally flat manifolds, see for instance [23]. One can now ask if the constructions developed here and in [16] extend to this more general context. This analysis will be developed elsewhere.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this way one constructs other examples of conformally flat manifolds, see for instance [23]. One can now ask if the constructions developed here and in [16] extend to this more general context. This analysis will be developed elsewhere.…”
Section: Introductionmentioning
confidence: 92%
“…It should though be pointed out that Dirac operators and associated Cauchy integral formulas have been introduced in a very general setting in [5,18,7]. The approach taken here and in [16] afford a more concrete viewpoint. The general intention is to find as explicit an approach to Clifford analysis as possible for reasonable choices of manifolds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [13] it is shown that C 1 (w, y) = 1 ωn y−w y−w n where ω n is the surface area of the unit sphere in R n . See also [11].…”
Section: Eigenvectors Of the Dirac-beltrami Operator On S Nmentioning
confidence: 99%
“…Basic aspects of Clifford analysis over spin manifolds have been developed in [6,7,37]. Further in [25,26,27,33,35,39] and elsewhere it is illustrated that the context of conformally flat manifolds provide a useful setting for developing Clifford analysis. Conformally flat manifolds are those manifolds which possess an atlas whose transition functions are Möbius transformations.…”
Section: Introductionmentioning
confidence: 99%